The institutional design of financial supervision and financial stability - Payne, J (Oxford University Press, 2020)
Since the inception of the European project, the creation of a single financial market has been a core policy goal. The ambition of the project subsequently expanded to include both economic and monetary union (EMU), a plan which came to fruition with the establishment of a single currency for euro area countries at the turn of the century. EMU has been said to be a ‘cornerstone of the European Union’, and may be regarded as a political as much as an economic endeavour.